1993
DOI: 10.1136/bjo.77.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic artery flow velocity in glaucomatous and normal subjects.

Abstract: (Br_J Ophthalmol 1993; 77: 25-29)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
95
1
12

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(112 citation statements)
references
References 15 publications
4
95
1
12
Order By: Relevance
“…When we are comparing blood-flow parameters between patients with different types of glaucoma, the extent of nerve damage, in addition to IOP, blood pressure, age and others, should be taken into consideration before conclusions are drawn. A study with transcranial Doppler ultrasound found a significantly slower mean flow velocity in NTG than in POAG (Rojanapongpun et al 1993). On the contrary, a later study with CDI found no significant difference in all flow parameters between these two groups if they were of similar age and with similar extent of field defects (Yamazaki & Hayamizu 1995).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…When we are comparing blood-flow parameters between patients with different types of glaucoma, the extent of nerve damage, in addition to IOP, blood pressure, age and others, should be taken into consideration before conclusions are drawn. A study with transcranial Doppler ultrasound found a significantly slower mean flow velocity in NTG than in POAG (Rojanapongpun et al 1993). On the contrary, a later study with CDI found no significant difference in all flow parameters between these two groups if they were of similar age and with similar extent of field defects (Yamazaki & Hayamizu 1995).…”
Section: Discussionmentioning
confidence: 93%
“…An earlier study with transcranial Doppler ultrasound reported reduced flow velocity in the ophthalmic artery in glaucoma (Rojanapongpun et al 1993).…”
mentioning
confidence: 87%
“…As various ocular [1][2][3][4][5][6][7][8][9] and systemic 9-20 vascular risk factors have been linked to the occurrence and progression of glaucomatous optic neuropathy, it would follow that they should be addressed by specific therapy. Despite this knowledge, however, the principal treatment objective remains reduction of intraocular pressure (IOP) using the large therapeutic arsenal available on the market.…”
Section: Introductionmentioning
confidence: 99%
“…Além da PIO, vários autores consideram que fatores circulatórios estejam envolvidos nos mecanismos de lesão do nervo óptico. Trabalhos com doppler colorido demonstraram diminuição do fluxo sangüíneo e aumento da resistência vascular na artéria oftálmica em pacientes com glaucoma em relação a indivíduos normais (4)(5)(6) . Assim, a pressão arterial (PA) poderia ter um papel importante no mecanismo de lesão, pois Descritores: Glaucoma; Pressão intra-ocular/efeito de drogas; Captopril/uso terapêutico; Propranolol/uso terapêutico; Hipertensão/quimioterapia; Cães Efeito de drogas utilizadas no tratamento de hipertensão arterial sistêmica sobre a pressão intra-ocular: estudo experimental no cão…”
unclassified